Profil Histologi Pankreas pada Kemanjuran Ekstrak Purifikasi Batang Galing terhadap Diabetes yang Diinduksi Streptozotocin pada Tikus Model Diabetes - Ilyas Y., Muhammad; Nuralifah; Dian Munasari Solo; Nirwati Rusli; Esti Badia (Universitas Ngudi Waluyo, 2024)
The galing plant (Cayratia trifolia L.Domin), one of the endemic plants in Southeast Sulawesi, is proven to contain bioactive flavonoid, alkaloid, and tannin compounds that have various pharmacological effects such as anti-diabetes and strong antioxidants, especially the stem, so it has the potential to be developed as an alternative to diabetes treatment. However, scientific information about the effects of pancreatic organ repair in diabetes still needs to be scientifically proven. The purpose of this study was to reveal the role of purified extract of galing stem on the repair of pancreatic organs of streptozotocin-induced diabetic model white rats. This study is an experimental study, with a post-test design with a control group design using 18 male white rats divided into normal control groups (non-DM), negative control (DM + Na.CMC), positive control (DM + glibenclamide 0.018 mg/kg BW) and treatment samples (DM + purified extract of galing stem 400 mg/kg BW). The results of this study indicate that the administration of purified extract of galing stem is proven to be able to repair damage to the pancreas organs in diabetic model rats shown by the improvement of the morphology of the pancreatic beta cell structure and an increase in the number of endocrine cells in the islets of Langerhans compared to the negative control that was not treated with the extract so that these findings as new scientific data for the development of potential anti-diabetic drugs from galing plants. ABSTRAK Tumbuhan galing (Cayratia trifolia L.Domin) salah satu tumbuhan endemik di Sulawesi Tenggara terbukti mengandung senyawa bioaktif flavanoid, alkaloid dan tanin yang memiliki berbagai efek farmakologi seperti anti diabetes dan antioksidan kuat khususnya bagian batang, sehingga berpotensi dikembangkan sebagai alternatif penanganan penyakit diabetes, namun informasi ilmiah tumbuhan ini tentang efikasi pada perbaikan organ pankreas pada diabetes masih perlu dibuktikan secara ilmiah. Tujuan penelitian ini untuk mengungkap peran ekstrak purifikasi batang galing terhadap perbaikan organ pankreas tikus putih model diabetes yang diinduksi streptozotocin. Penelitian ini adalah penelitian eksperimental, dengan desain rancangan post test with control group design menggunakan 18 ekor tikus putih jantan dibagi dalam kelompok kontrol normal (non DM), kontrol negatif (DM+Na.CMC), kontrol positif (DM+glibenklamid 0,018 mg/kg BB) dan perlakuan sampel (DM+ekstrak purifikasi batang galing 400 mg/kg BB). Hasil penelitian ini menunjukan bahwa pemberian ekstrak terpurifikasi batang galing terbukti dapat memperbaiki kerusakan organ pankreas pada tikus model diabetes yang ditunjukan adanya perbaikan morfologi struktur sel beta pangkreas dan terjadi peningkatan jumlah sel endokrin di pulau langerhans dibandingkan dengan kontrol negatif yang tidak diberi perlakuan ekstrak, sehingga temuan ini sebagai data ilmiah baru untuk pengembangan obat anti diabetes yang potensil dari tumbuhan galing.